The Influence of Work Motivation, Compensation, and Work Environment on Employee Performance at PT Jaya Kencana - Gatot Hery Djatmika; Ningsih, Putu Tirta Sari; Budi Harsono; Dewi Fitriani (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of work motivation on employee performance at PT. Jaya Kencana, the effect of compensation on employee performance at PT. Jaya Kencana, the influence of the environment on the performance of employees at PT. Jaya Kencana, and the effect of work motivation, compensation, and work environment simultaneously on employee performance at PT. Jaya Kencana. The method used in this research is descriptive quantitative method. This research was conducted by looking for primary data with a sample size of 100 employees of PT. Jaya Kencana. The data were processed by statistical analysis with validity, reliability, classical assumption test, multiple linear regression analysis, hypothesis testing through t test and F test, and analysis of the determinant coefficient (R). From the results of the analysis, it shows that the results of the multiple linear regression test are Y= 5.526 + 0.481X1 + 0.133X2 + 0.357X3 and for the F test results it is found that H0 is rejected and Ha is accepted with a value of Fcount 57.663 > Ftable 2.99 at significant 0.000 < Ftable 0.05. So the F test shows that work motivation, compensation, and work environment together (simultaneously) have a positive and significant effect on employee performance at PT. Jaya Kencana with the percentage of the coefficient of determination of 63.2%.